Speaking in bones : a novel - Reichs, Kathy (Reichs, Kathy. Temperance Brennan series., 2015)
"Hazel 'Lucky' Strike--a strident amateur detective who mines the Internet for cold cases--comes to Brennan with a tape recording of an unknown girl being held prisoner and terrorized. Strike is convinced the voice is that of eighteen-year-old Cora Teague, who went missing more than three years earlier. Strike is also certain that the teenager's remains are gathering dust in Temperance Brennan's lab. Brennan has doubts about working with a self-styled websleuth, but when the evidence seems to add up, Brennan's next stop is the treacherous backwoods where the chilling recording (and maybe Cora Teague's bones) were discovered"--Dust jacket flap.